A zero-dissipative Runge-Kutta-Nystrom method with minimal phase-lag - Senu, Norazak; Suleiman, Mohamed; Ismail, Fudziah; Othman, Mohamed (Hindawi Publishing Corporation, 2010)
An explicit Runge-Kutta-Nyström method is developed for solving second-order differential equations of the form where the solutions are oscillatory. The method has zero-dissipation with minimal phase-lag at a cost of three-function evaluations per step of integration. Numerical comparisons with RKN3HS, RKN3V, RKN4G, and RKN4C methods show the preciseness and effectiveness of the method developed.